A systematic evidence map of conservation knowledge in Chilean Patagonia - Jose Martinez-Harms, Maria; Armesto, Juan J.; Carlos Castilla, Juan; Astorga, Anna; Aylwin, Jose; Buschmann, Alejandro H.; Castro, Victoria; Daneri, Giovanni; Fernandez, Miriam; Fuentes-Castillo, Taryn; Gelcich, Stefan; Gonzalez, Humberto E.; et al. (My University, 2022)
Mechanisms that reliably and efficiently guide practitioners to find relevant evidence are urgent for conservation decision-making in Chilean Patagonia. The objective of this study was to systematically collect, characterize, and synthesize the extensive evidence about conservation knowledge in Chilean Patagonia focusing on the impacts of global change drivers on ecosystems and human-nature relationships, identifying knowledge gaps, and providing policy recommendations. The quality of the evidence was assessed through a predefined level-of-evidence hierarchy scale, applied to a sample of the studies reviewed. We compiled similar to 1000 studies documenting that evidence focusing on terrestrial and marine ecosystems has grown exponentially. For terrestrial ecosystems, most studies have addressed climate change, habitat change, and invasive species; while for marine ecosystems, studies have focused on pollution, invasive species, and habitat change. We identified that an important gap is the study of the social dimensions of conservation, and future efforts should focus on incorporating traditional and local knowledge as this can help point the way to ecosystem conservation. The appraisal of the quality of the evidence showed that similar to 80% of the sample represented reliable evidence with underlying data and an experimental design. Enhanced efforts to deliver this evidence to decision-makers in a user-friendly format for evidence uptake in conservation policy are urgent. In this review, we provide a tool that can help practitioners to find evidence reliably to improve decision-making for the conservation of ecosystems in Chilean Patagonia.
Keywords: conservation decision making; global change drivers; human-nature relationships; interdisciplinary process; protected areas